1980
DOI: 10.1007/bf00270473
|View full text |Cite
|
Sign up to set email alerts
|

IS4 is still found at its chromosomal site after transposition to galT

Abstract: IS4-DNA has been hybridized to separated DNA fragments of E. coli K12 strain M28 and to three mutants caused by transposition of IS4 to galT. The parental strain shows one band hybridizing to IS4 representing one copy of IS4 in the chromosome. The mutants have this copy retained and show in addition a second band corresponding to the IS4 copy in galT. The experiments support the hypothesis that transposition of IS4 is accompanied by replication of the element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…IS2 insertion occurs at only two sites in the operator domain (29), and IS4 has been repeatedly observed to integrate into a single site in the galTgene (30). Thus, the apparent specificity of insertion in eps is consistent with integration properties of IS.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…IS2 insertion occurs at only two sites in the operator domain (29), and IS4 has been repeatedly observed to integrate into a single site in the galTgene (30). Thus, the apparent specificity of insertion in eps is consistent with integration properties of IS.…”
Section: Discussionmentioning
confidence: 83%
“…Cosmid vector "arms" were ligated with donor DNA by the method of Franklin (18). Sau3A partially digested donor DNA in the size range of [25][26][27][28][29][30][31][32][33][34][35][36][37] kilobase pairs (kbp) was prepared as described by Maniatis et al (19). In vitro packaging of ligated DNA was accomplished by using Gigapack Plus (Stratagene) A DNA packaging extracts according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, by position effect analysis (7), Asheshov and Dykes concluded that the penicilhinase gene, originally located on the chromosome, was duplicated, with one copy being retained on the chromosome and the second being incorporated into the plasmid, and that both of the genes expressed their trait simultaneously. (202), has been observed with IS4 in gram-negative bacteria (97). Up to this time, among plasmids containing the 8-lactamase gene, precise physical genetic maps of plasmids pI258, pI524, and pI6187 of incompatibility group I and pII147 of group II VOL.…”
Section: Pathogenic Bacteriamentioning
confidence: 97%
“…Secondly, excision could also account for the loss, as has been observed with other insertion elements (15). For instance, IS1mediated excision in E. coli removed more than 1 kb of flanking chromosome from either side of the element (34), while IS4 excision has been observed to delete chromosomal sequences from both sides of this element (24). Excision would typically involve the transposase of the insertion sequence and would not involve homologous recombination, so the losses here of intact DVR units would not be compatible with such a mechanism.…”
Section: Discussionmentioning
confidence: 99%